Penerapan Model UTAUT Untuk Menganalisis Penerimaan dan Penggunaan Sistem Informasi E-Office (Studi Kasus: PT ABCX) - Rahma Apriyani; Desi Pibriana (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Abstract PT ABCX which is a company engaged in the loading and unloading of containers has an E-Office information system that aims to carry out the company's internal operational activities. So far, the company does not know the factors that influence the acceptance and use of the ABCX E-Office information system, therefore a measurement of the level of acceptance and use of the ABCX E-Office information system will be carried out in supporting the performance of employees in each work unit using the UTAUT methodology. The data in this study were analyzed using SPSS software and the research model was tested with the Structural Equation Modeling (SEM) application which will be analyzed using AMOS 26 software. The results of this study indicate that interest in utilization (BI) is significantly influenced by business expectations (EE) and social influence (SI) while usage behavior (UB) is significantly influenced by interest in utilization (BI). It can be concluded that employees who use the ABCX E-Office information system find it easiest to use and easy to understand and there is also influence and support from the company so that PT ABCX employees are interested in using the ABCX E-Office information system.